Determination of deviatoric elastic strain and lattice orientation by applying digital image correlation to Laue microdiffraction images: the enhanced Laue‐DIC method. (3rd December 2015) - Zhang, F. G.; Castelnau, O.; Bornert, M.; Petit, J.; Marijon, J. B.; Plancher, E.
Abstract : A new method of determining the deviatoric elastic strain and lattice orientation from Laue microdiffraction images is presented. Standard data treatment methods can suffer from the difficulty of precisely pinpointing the positions of diffraction peaks on two‐dimensional Laue images. In a previous article, digital image correlation (DIC) was introduced for the treatment of Laue images, leading to the so‐called Laue‐DIC method. This performed better than the standard method in terms of the deviatoric elastic strain increment and relative rotation from one lattice to another, particularly when the shape of the Laue spots departs from regular ellipsoids. The present work intends to push forward the Laue‐DIC method, aiming to determine the deviatoric elastic strain and lattice orientation, as well as the calibration parameters. The performance of this new method, named enhanced Laue‐DIC, is assessed by modeling the spot displacements and accounting for random fluctuations relevant for typical experimental conditions. When the enhanced Laue‐DIC method is applied to the case of an in situ deformed Si crystal, the obtained standard deviation of local stress is of the order of 1–2 MPa, while the calibration parameters are optimized to high accuracy.